Transcriptomic Profiling and Physiological Responses of Halophyte Kochia sieversiana Provide Insights into Salt Tolerance - Zhao, Long; Yang, Zongze; Guo, Qiaobing; Mao, Shun; Li, Shaoqiang; Sun, Fasheng; Wang, Huan; Yang, Chunwu (Frontiers in Plant Science, 2017)
Abstract Halophytes are remarkable plants that can tolerate extremely high-salinity conditions, and have different salinity tolerance mechanisms from those of glycophytic plants. In this work, we investigated the mechanisms of salinity tolerance of an extreme halophyte, Kochia sieversiana (Pall.) C. A. M, using RNA sequencing and physiological tests. The results showed that moderate salinity stimulated the growth and water uptake of K. sieversiana and, even under 480-mM salinity condition, K. sieversiana maintained an extremely high water content. This high water content may be a specific adaptive strategy of K. sieversiana to high salinity. The physiological analysis indicated that increasing succulence and great accumulations of sodium, alanine, sucrose and maltose may be favorable to the water uptake and osmotic regulation of K. sieversiana under high-salinity stress. Transcriptome data indicated that some aquaporin genes and potassium (K+) transporter genes may be important for water uptake and ion balance, respectively, while different members of those gene families were employed under low- and high-salinity stresses. In addition, several aquaporin genes were up-regulated in low- but not high-salinity stressed roots. The highly expressed aquaporin genes may allow low-salinity stressed K. sieversiana plants to uptake more water than control plants. The leaf K+/root K+ ratio was enhanced under low- but not high-salinity stress, which suggested that low salinity might promote K+ transport from the roots to the shoots. Hence, we speculated that low salinity might allow K. sieversiana to uptake more water and transport more K+ from roots to shoots, increasing the growth rate of K. sieversiana.